Investigation of Empathy Skills and Moral Decision-Making Attitudes in Athlete Students in Terms of Some Variables - Serhat Turan; Ercan Çirmi (Journal of Educational Issues, 2024)
It is observed that the appearance of aggression and violent anti-social behavior in sports contradicts the Olimpia culture inherent in sports. Therefore, this research was conducted in order to reveal the causes and consequences of negative behaviors observed in sports, to examine the empathy skills and moral decision-making attitudes of athletes in terms of different variables. The research was arranged by the screening survey model. A total of 319 athletes, 180 men, and 139 women, engaged in individual and team sports in the city where the research was conducted, voluntarily participated in this research. Personal information form, “Prediction in Sports and Empathy in Sports” and “Attitudes to Moral Decision-making in Youth Sport Questionnaire” were applied to the participants. In the analysis of the data, the Manova test and the LSD test were used to determine the source of the difference. As a result of the research, while a significant difference was found in favor of men in terms of gender in empathy skills(p < .05); there was not found a significant difference in terms of sports branch and sports year(p > .05). In terms of the sports year variable, the moral decision-making attitude scores of individuals who have just started sports (0-2 years) compared to individuals who have been doing sports for a long time(9+ years) were found to be higher and this result was found to indicate a statistically significant difference(p < .05). There was not found a significant difference in moral decision-making attitudes scores in terms of sports year and gender.